2012
DOI: 10.1111/j.1468-3148.2012.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Reliability and Validity of theSocial–MoralAwarenessTest

Abstract: There is early evidence of the construct validity and reliability of the SMAT. Further assessment of the validity of the SMAT will be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 46 publications
2
15
1
1
Order By: Relevance
“…Better ToM performance will predict higher social-moral awareness scores, as found by Livesey et al (2012).…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…Better ToM performance will predict higher social-moral awareness scores, as found by Livesey et al (2012).…”
mentioning
confidence: 68%
“…Kohlberg (1969) suggested that there are six stages over three levels of moral development: pre-conventional (reasoning based on consequences); conventional (reasoning based on approval from others/group norms); and post-conventional (reasoning based on general rather than individual benefit, and conscience). Gibbs (1979) and Gibbs et al (1992) built upon Kohlberg’s work to develop a socio-moral stage theory (Livesey et al , 2012). The socio-moral stage theory categorises the justifications people give for their behaviour into “immature”, where decisions are rule-based (stage 1) or based upon personal gain (stage 2), and “mature”, where decisions are made based on understanding of emotional states (stage 3), and on concepts such as rights and values (stage 4) (Gibbs, 1979; Gibbs et al , 1992).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Se han encontrado otras aportaciones en esta misma línea de investigación que apuntan a la extracción de índices de responsabilidad social, a los que dan seguimiento entidades como el Observatorio de Responsabilidad Social Corporativa (Observatorio de RSC, 2018;Galán, 2012). Respecto a la responsabilidad social universitaria tomamos como referencia para este artículo las aproximaciones de indicadores para la evaluación de la Responsabilidad Social Universitaria de Larrán (2011Larrán ( ,2014, Vallaeys (2006Vallaeys ( , 2012 e Yfarraguerri (2014), el índice integral para evaluar la responsabilidad social universitaria (Viteri-MoyaI, Jácome-VillacresI, Medina-LeónII y Neydalis, 2012), la validación de un constructo subyacente en una escala de evaluación del impacto de la investigación educativa (Díaz-Costa, Fernández-Cano, Faouzi y Henríquez, 2015) y la exploración de la fiabilidad y validez de pruebas de conciencia social y moral (Livesey, Dodd, Pote & Marlow, 2012).…”
Section: Introducción Y Estado De La Cuestiónunclassified